SP0122 Kinase Inhibitors: Clinical Aspects. (15th July 2016) - Firestein, G.S.
Abstract : Kinases play a critical role in inflammatory disease and immune regulation. They are critical molecules that transduce signals from the environment, including cytokines and toxic exposures. Their participation in human rheumatic disease has been confirmed through the testing and introduction of kinase inhibitors to treat various immune-mediated diseases. Janus kinase inhibitors, for example, are effective in rheumatoid arthritis, psoriasis and many others. These observations create opportunities for targeting other pathways and kinases that play a role in B cell activation and differentiation, stress responses, and cytokine signaling. Our experience with kinase inhibitors also demonstrates that the specific kinase and its inhibitor must be carefully matched to the pathogenic process. Several unsuccessful clinical development programs, such as p38 MAP kinase or Syk, show that the balance between efficacy, clinical indication, and toxicity need to be carefully considered. The future, however, is bright because there is an abundance of potential targets. Carefully designed clinical trials, use of biomarkers to stratify patients, and patience will pay off we new and creative ways to treat our patients. Disclosure of Interest: None declared